2008
DOI: 10.1074/jbc.m801728200
|View full text |Cite
|
Sign up to set email alerts
|

PAK Is Regulated by PI3K, PIX, CDC42, and PP2Cα and Mediates Focal Adhesion Turnover in the Hyperosmotic Stress-induced p38 Pathway

Abstract: Fractionation of brain extracts and functional biochemical assays identified PP2C␣, a serine/threonine phosphatase, as the major biochemical activity inhibiting PAK1. PP2C␣ dephosphorylated PAK1 and p38, both of which were activated upon hyperosmotic shock with the same kinetics. In comparison to growth factors, hyperosmolality was a more potent activator of PAK1. Therefore we characterize the PAK signaling pathway in the hyperosmotic shock response. Endogenous PAKs were recruited to the p38 kinase complex in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 58 publications
3
45
1
Order By: Relevance
“…A well-described downstream target of activated Cdc42 is serine/threonine protein kinase 1 that stimulates the FGF signaling pathway [52][53][54]. Interestingly, Par6 overexpression is able to induce EGF/ FGF independence of epithelial cells, in a Cdc42-and aPKCdependent manner [55], providing further evidence for a possible link between apical polarity complex proteins and FGF signaling.…”
Section: A Model For Apical Polarity Protein Signaling In Neuroepithementioning
confidence: 91%
“…A well-described downstream target of activated Cdc42 is serine/threonine protein kinase 1 that stimulates the FGF signaling pathway [52][53][54]. Interestingly, Par6 overexpression is able to induce EGF/ FGF independence of epithelial cells, in a Cdc42-and aPKCdependent manner [55], providing further evidence for a possible link between apical polarity complex proteins and FGF signaling.…”
Section: A Model For Apical Polarity Protein Signaling In Neuroepithementioning
confidence: 91%
“…We have previously shown that GF-activated PAK serves as a scaffold protein of the Akt1 pathway that regulates the target specificity of Akt1 (Higuchi et al, 2008). Since it has been reported that PAK is localized at FAs (Stoletov et al, 2001;Brown et al, 2002;Chan et al, 2008;Delorme-Walker et al, 2011) and that PAK forms a complex with FAK (Stoletov et al, 2001), it is possible that PAK may also serve as a scaffold protein that facilitate the association between Akt1 and FAK at FAs, resulting in Akt1-mediated phosphorylation and activation of FAK in GF-stimulated cells. Since it has been shown in a recent study that Ser695 is necessary for pressure-induced activation of FAK in Caco-2 cells (Wang and Basson, 2011), it would also be worth examining whether the PAK-Akt1 pathway is also involved in pressure-induced activation of FAK in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian group I Paks (Pak1, Pak2, and Pak3) are capable of complementing a Ste20 deletion in yeast; in contrast, the more divergent group II Paks (Pak4, Pak5, and Pak6) are unable to do so (17). Evidence that mammalian group I Paks function as MAP4Ks is lacking, but they can serve as links between Cdc42 (or Rac1) and p38, though the details are less clear than in yeast (21)(22)(23)(24).…”
mentioning
confidence: 99%